2009
DOI: 10.1097/jcp.0b013e3181aba68f
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Neural Network Model for the Prediction of Obsessive-Compulsive Disorder Treatment Response

Abstract: Several patients with obsessive-compulsive disorder (OCD) who are refractory to adequate treatment with first-line treatments are considered treatment-resistant. Further surveys were to be implemented to explore the outcome predictors of the antiobsessional response. Such study was aimed at building a model suitable to predict the final outcome of a mixed OCD pharmacologic and nonpharmacologic treatment approaches. We studied 130 subjects with OCD who underwent pharmacologic (with selective serotonin reuptake … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 45 publications
0
18
0
2
Order By: Relevance
“…With only 50% of patients experiencing treatment response to first-line agents, and an adequate antidepressant trial requiring several weeks before symptom improvement becomes evident, machine-learning methods have the potential to significantly reduce the duration of patient suffering. Outside the scope of depression, these techniques have shown promise in predicting treatment response in other various other psychiatric diseases, including schizophrenia and obsessive–compulsive disorder ( Khodayari-Rostamabad et al, 2010 , Salomoni et al, 2009 ). Therefore, advances in development of machine-learning are likely to have wide-ranging implications throughout psychiatry, regardless of the specific disease to which they are first applied.…”
Section: Future Directionsmentioning
confidence: 99%
“…With only 50% of patients experiencing treatment response to first-line agents, and an adequate antidepressant trial requiring several weeks before symptom improvement becomes evident, machine-learning methods have the potential to significantly reduce the duration of patient suffering. Outside the scope of depression, these techniques have shown promise in predicting treatment response in other various other psychiatric diseases, including schizophrenia and obsessive–compulsive disorder ( Khodayari-Rostamabad et al, 2010 , Salomoni et al, 2009 ). Therefore, advances in development of machine-learning are likely to have wide-ranging implications throughout psychiatry, regardless of the specific disease to which they are first applied.…”
Section: Future Directionsmentioning
confidence: 99%
“…Some retrospective studies investigating the influence of OCD symptom factors on treatment response found that hoarding and saving symptoms in patients with OCD were associated with poor response to pharmacotherapy with serotonin reuptake inhibitor (SRI) medications (Black et al 1998, Winsberg et al 1999, Mataix-Cols et al 1999, Stein et al 2007 & 2008, Salomoni et al 2009), but many others have failed to replicate this association (Saxena 2011). Several studies found that hoarding/saving symptoms had no significant effect on response to treatment in OCD patients (Alonso et al 2001, Ferrao et al 2006, Erzegovesi et al 2001, Shetti et al 2005, Landeros-Weisenberger et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of hoarding symptoms on the Y-BOCS symptom checklist was associated with poor treatment response regardless of the type of pharmacological treatment. Another study examined 130 adult patients with OCD who received SSRIs alone or with low dose of an atypical antipsychotic, risperidone, and/or behavioral therapy (using exposure and response prevention techniques) (Salomoni et al 2009). Using factors identified from the Y-BOCS, hoarding was again found to be a predictor of worse outcome.…”
Section: Medication Studies Showing Poor Treatment Responsementioning
confidence: 99%